He still moves stones - Lucado, Max (Word Pub, 1993)
This is a most powerful and empowering book. Max Lucado, a spiritual writer, refers to the way Christ moves the stones (obstacles) in your path with this title. Such relevant issues include feeling shame for past behaviors, when others let us down, facing discouragement, having a bad attitude and dealing with difficult relatives.